Genotype × environment interactions in grain quality traits and yield of barley grown in Kostanay and Almaty regions (Eurasian Journal of Ecology, 2021)
Barley is one of the most important cereal crops in the world and the second cereal in Kazakhstan. Traditionally barley is cultivated in the northern part of Kazakhstan, however, due to high genetic plasticity, barley has a great potential for adaptation in different climatic conditions. High levels of grain quality and yield are major indicators of good adaptation. In this study 357 spring barley cultivars and breeding lines from Kazakhstan and the USA were grown in two regions of Kazakhstan (Kostanay and Almaty regions). The collection was analyzed using seven grain quality and two yield-related traits, including grain protein, starch, lipids, ash, cellulose and moisture contents, plumpness, as well as thousand kernel weight and yield per square meter. A significantly large environmental impact was observed for thousand kernel weight and grain protein content. Grain starch, lipids content, and yield per square meter showed stability in two regions and were mostly controlled by the genotype. Correlations of high yield with high grain protein and low starch content were observed in both north and south-east regions. In general, the field trials assessment showed that barley cultivation in Kostanay region suits well malting-oriented breeding and in Almaty region for animal feed-oriented breeding. Based on the obtained results, the list of barley cultivars and promising breeding lines with high yield and grain quality was selected as the optimal breeding source in Kostanay and Almaty regions.Key words: Hordeum vulgare L., malting barley, livestock feed barley, genotype × environment.